Repeated Recovery of Staphylococcus saprophyticus From the Urogenital Tracts of Women: Persistence Vs. Recurrence - M. E. Rupp; J. Han; R. V. Goering (Hindawi Limited, 1995)
Objective: The purpose of this study was to determine whether colonization was persistent or recurrent in a small group of women who had repeated recovery of Staphylococcus saprophyticus from their urogenital tracts.